Social anxiety disorder in medical students: socio-demographic correlates - Jogdande, Amit J.; Gupta, Anurag (International Journal Of Community Medicine And Public Health, 2017)
Background: The aims and objectives were to find types of social anxiety disorders among MBBS students; to study association of socio demographic factors and social anxiety disorder among MBBS students. Methods: This cross sectional study was conducted on 150 medical students of 2nd and 3rd year who were willing to participate. Students were asked to fill pretested structured pro-forma, maintaining all the privacy. The social phobia inventory (SPIN) questionnaire was used to diagnose SAD. Mild social anxiety is considered as normal. Analysis was done using the SPSS Version 20. Results: Out of 150 medical students, mostly (54%) were not having SAD and 46% of students who were having SAD. 27% of students were having mild SAD and 19% of students were having significant SAD. Mild social anxiety is considered as normal. Factors as gender, score in 10th standard, score in 12th standard, mother’s education, student’s residence after age of 18 years, student’s either of parents are dead or alive, were found to be significantly associated with SAD. After applying multiple logistic regression it was found that Gender (female), <75% in 10thStd, <75% in 12thStd and Mothers education <12th standard were found to be significantly associated with SAD in students. Conclusions: Out of 150 medical students, 19% of students were having significant SAD. Gender (female), <75% in 10thStd, <75% in 12thStd and Mothers education <12th standard were found to be significantly associated with SAD in students.